Phenotypic CRISPR screens identify NLRX1 as an essential activator of the human mitochondrial permeability transition - William C. Valinsky; Robert P. Ray; Kathy S. Schaefer; Jonathan B. Grimm; Carla Nicolini; Luke D. Lavis; David E. Clapham (Proceedings of the National Academy of Sciences, 2026)
The mitochondrial permeability transition (mPT) is an evolutionarily conserved destructive process that permeabilizes the inner mitochondrial membrane in response to calcium overload. The molecular mechanism underlying the mPT is not established. To unambiguously identify essential proteins, we designed two phenotypic assays for mitochondrial calcium overload and applied them to FACS-based CRISPR screening in human cells, ultimately evaluating 19,113 genes. The first screen studied mitochondrial membrane potential (MMP) collapse in response to calcium overload. Top-ranked genes were the essential proteins of the mitochondrial calcium uniporter complex, MCU and EMRE, reflecting that the calcium-induced MMP collapse results from mitochondrial calcium entry and not the mPT. The second screen measured the permeability of the inner mitochondrial membrane. Here, the fluorescent interaction of a membrane impermeant ~600 Da dye and a mitochondrial-targeted HaloTag protein was studied under mPT activating conditions; calcium overload and the thiol-reactive molecule phenylarsine oxide. With secondary validation, we identified four protein-encoding genes that delayed or prevented the mPT under knockout: NF2, REST, BPTF, and NRLX1. Knockout of the nonmitochondrial proteins BPTF, NF2, or REST increased mitochondrial calcium retention capacity (CRC). However, calcium release or sensitivity to cyclosporin A (CsA) persisted, indicative of mPT sensitizers. Only knockout of the mitochondrial matrix protein, NLRX1, increased CRC, abolished calcium release, and was CsA-insensitive. This top-ranked hit of the mitochondrial permeability screen meets the definition of an essential mPT activator. Integral membrane proteins, including all previously proposed mPT candidates, were not essential activators.